Cobalt nanoparticles supported on ionic liquid‐functionalized multiwall carbon nanotubes as an efficient and recyclable catalyst for Heck reaction. (13th September 2015) - Hajipour, Abdol R.; Khorsandi, Zahra; Karimi, Hirbod
Abstract : A novel and environmentally friendly cobalt nanoparticle catalyst supported on ionic liquid‐functionalized multiwallcarbon nanotubes was successfully prepared and evaluated as a heterogeneous catalyst for theMizoroki–Heck reaction . Several reaction parameters, including type and amount of solvent and base, were evaluated. This nanocatalyst could also be recovered and reused at least six times without any discernible decrease in itscatalytic activity . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper presents a heterogeneous catalyst of deposit nano cobalt on supported imidazolium ionic liquid on multi‐walled carbon nanotubes, which is an air stable catalyst, facile and efficient strategy for the Heck reaction without expensive palladium and toxic ligands.